2005
DOI: 10.1162/0898929054985473
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Voice Onset Time: An fMRI Investigation of Phonetic Category Structure

Abstract: This study explored the neural systems underlying the perception of phonetic category structure by investigating the perception of a voice onset time (VOT) continuum in a phonetic categorization task. Stimuli consisted of five synthetic speech stimuli which ranged in VOT from 0 msec ([da]) to 40 msec ([ta]). Results from 12 subjects showed that the neural system is sensitive to VOT differences of 10 msec and that details of phonetic category structure are retained throughout the phonetic processing stream. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
119
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 41 publications
21
119
2
1
Order By: Relevance
“…Competition and the inferior frontal gyri-Similar to data reported in Blumstein et al (2005), activation emerged in the left inferior frontal gyrus as a function of the degree of competition expected to arise from the contrasting phonetic category. Namely, there was increased activation for the near-boundary stimuli compared to either the exemplar or extreme stimuli.…”
Section: Fmri Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Competition and the inferior frontal gyri-Similar to data reported in Blumstein et al (2005), activation emerged in the left inferior frontal gyrus as a function of the degree of competition expected to arise from the contrasting phonetic category. Namely, there was increased activation for the near-boundary stimuli compared to either the exemplar or extreme stimuli.…”
Section: Fmri Resultssupporting
confidence: 67%
“…Each functional volume acquisition lasted 1200 msec, followed by 20 msec of scanner-added time, plus 780 msec of added silence which was programmed into the acquisition sequence. The result was a clustered design (Blumstein et al, 2005;Edmister, Talavage, Ledden, & Weisskoff, 1999) in which each TR consisted of 1200 msec of scanning, followed by 800 msec of silence, for a total TR of 2 seconds.…”
Section: Mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The NAPP model of Nearey and Hogan (1986) is also focused on identification tasks. Feldman et al (2009) were the first to introduce the idea that discrimination tasks involve inferring a continuous value T , which is a denoised version of the stimulus S. This focus on recovering continuous detail from the speech signal provides an advantage over previous models that have treated only the classification problem, and is consistent with evidence that listeners perceive acoustic detail (Andruski et al, 1994;Blumstein et al, 2005;Joanisse et al, 2007;Pisoni and Tash, 1974;Toscano et al, 2010). The model explains how the perceptual process leads to effects we see in both identification and discrimination, not just categorical effects in identification.…”
Section: Discussionmentioning
confidence: 70%
“…They showed that stimuli with initial stop consonant VOTs near the category center exhibited a stronger priming effect for semantically-related following stimuli, and that non-central values also elicited longer reaction times. Finally, at the neural level, an fMRI study by Blumstein et al (2005) showed that there are robust neural correlates to subphonemic VOT differences in stimuli. In related work looking at event-related potentials during word categorization in an auditory oddball task, Toscano et al (2010) showed that listeners are sensitive to fine acoustic differences in VOT independent of the categorization.…”
Section: Stop Consonant Effectsmentioning
confidence: 99%